Modelling biohydrogen production from residual hydrocarbons by immobilized bacteria using COMSOL multiphysics - Abutu, David; Wan Mohd Hafizuddin, Wan Yussof; Nyah, Francis; Nwaichi, Peter Ikechukwu; Umunnawuike, Chika; Agi, Augustine Aja (Elsevier Ltd., 2026)
Growing demand for low-carbon energy has increased interest in biological hydrogen production from unconventional resources. Residual hydrocarbons in depleted oil reservoirs offer a potential substrate for thermophilic biohydrogen generation, but integrated experimental modelling studies under reservoir conditions remain limited. This study investigates biohydrogen generation from residual hydrocarbons within a simulated media mimicking a depleted oil reservoir, combining batch experiments with COMSOL Multiphysics® modelling. Laboratory trials at 68.4 °C showed a progressive increase in hydrogen concentration from 0 to 7.63 mmol L−1 within 168 h, corresponding to a 37 % substrate utilization. A three-dimensional axisymmetric domain was implemented in COMSOL Multiphysics by coupling the transport of diluted species, coefficient form PDE, and heat transfer in porous media interfaces to simulate substrate diffusion, microbial reaction kinetics, and thermal effects within the porous reservoir system. The model achieved close agreement with experimental data (R2 = 0.985; mean deviation = 7.8 %). Simulated peak hydrogen concentration reached 7.45 mmol L−1 at 168 h, with maximum biomass density of 1.8 × 107 cells cm−3 localized around immobilized beads. Sensitivity analysis indicated that a 10 % decrease in substrate diffusivity reduced hydrogen yield by 8.6 %, while temperatures above 72 °C decreased microbial activity by 12 %. Distribution plots revealed hydrogen accumulation zones extending 2-3 mm from bead surfaces, governed by local diffusion–reaction coupling. Model-predicted hydrogen productivity of 1.05 mmol L−1 h−1 validated the experimental average of 1.09 mmol L−1 h−1. These findings show residual hydrocarbons can support thermophilic biohydrogen in depleted reservoirs, and COMSOL modelling effectively predicts and optimizes subsurface production processes.